2013
DOI: 10.1111/exd.12101
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a attenuates Wnt/β‐catenin signalling in human dermal papilla cells

Abstract: Abstract:Findings of recent studies have demonstrated modulation of Wnt/b-catenin signalling by Wnt5a, which is highly expressed in hair follicular dermal papilla (DP) in vivo. Here, we investigated the question of whether Wnt5a can affect canonical Wnt/b-catenin signalling in DP cells. Treatment with Wnt5a resulted in attenuation of Wnt3a-mediated elevation of b-catenin signalling, which was increased by Wnt5a siRNA transfection in cultured DP cells, as examined by reporter assay. In addition, treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 25 publications
(28 reference statements)
2
24
0
Order By: Relevance
“…Although both Wnt3a and Wnt5a belong to the Wnt family, the functions of the two proteins are counteractive. Previous studies reported that Wnt3a and Wnt5a activate different, even opposing, signaling profiles in other cells such as human dermal papilla cells (Kwack et al 2013), hematopoietic stem cells (Nemeth et al 2007), microglia (Halleskog and Schulte 2013), and several cell lines (Topol et al 2003). In agreement with these observations, we found that Wnt3a and Wnt5a counteracted the hyperoxia-induced inhibition of transdifferentiation of AECIIs to AECIs in primary AECIIs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although both Wnt3a and Wnt5a belong to the Wnt family, the functions of the two proteins are counteractive. Previous studies reported that Wnt3a and Wnt5a activate different, even opposing, signaling profiles in other cells such as human dermal papilla cells (Kwack et al 2013), hematopoietic stem cells (Nemeth et al 2007), microglia (Halleskog and Schulte 2013), and several cell lines (Topol et al 2003). In agreement with these observations, we found that Wnt3a and Wnt5a counteracted the hyperoxia-induced inhibition of transdifferentiation of AECIIs to AECIs in primary AECIIs.…”
Section: Discussionsupporting
confidence: 91%
“…The counteractive effect of Wnt3a and Wnt5a has been reported in human dermal papilla cells (Kwack et al 2013) and lipopolysaccharide-induced mouse primary microglia (Halleskog and Schulte 2013). However, the role of Wnt3a and Wnt5a in hyperoxia-induced lung diseases has not been studied.…”
mentioning
confidence: 99%
“…It is also associated with β -catenin/TCF4 complex, and knockdown of Fermt2 leads to loss of β -catenin mediated transcription [44], ultimately affecting myogenic development. Other effectors of the β -catenin/TCF4 complex, such as Wnt, are known to be required for the hair inducing property of DP cells [45]. Background population proteins were also localized by immunofluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…The Wnt5a-mediated non-canonical Wnt pathway has been reported to antagonize the b-catenin-dependent canonical Wnt pathway by promoting the phosphorylation of b-catenin in various contexts (15,16). Most recently, Wnt5a was reported to attenuate Wnt3a-mediated elevation of b-catenin signal in hair follicle dermal papilla cells (17). Therefore, elevated levels of b-catenin phosphorylation caused by excessive epithelial Wnt5a is most likely responsible for the anagen impairment in TG mice.…”
Section: Discussionmentioning
confidence: 99%